2001
DOI: 10.1017/s0012162200001481
|View full text |Cite
|
Sign up to set email alerts
|

Effect of secretin on children with autism: a randomized controlled trial

Abstract: To determine the effect of intravenous porcine secretin on autistic behaviours in children aged 2 to 7 years, the effects of secretin on (1) performance on a standardized language measure, and (2) autistic behaviours, as rated by parents and child development professionals was examined. Employing a randomized, double-blind, placebo-controlled design, 95 participants were assigned to one of two groups and administered a single dose of either secretin or placebo. A follow-up assessment was conducted 3 weeks afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…To the authors' knowledge, nine double-blind, placebo-controlled trials of single-dose secretin (Carey et al, 2002;Coniglio, Lewis, Lang, & Burns, 2001;Corbett, Khan, Czapansky-Beilman, & Brady, 2001;Dunn-Geier, Ho, Auersperg, & Coyle, 2000;Kern, Miller, Evans, & Trivedi, 2002;Malloy et al, 2002;Owley et al, 2001;Sandler et al, 1999;Unis et al, 2002), two double-blind, placebo-controlled studies with multiple secretin doses (Roberts, Weaver, Brian, & Bryson, 2001;Sponheim, Oftedal, & Helverschou, 2002), two open-label single-dose trials (Chez, Buchanan, & Bagan, 2000; and one study of the impact of secretin on sleep in autistic children have been completed (Honomichl, Goodlin-Jones, Burnham, Hansen, & Anders, 2002). The two open-label trials, combined, included 44 autistic children and 34 children with PDD not otherwise specified (Chez et al, 2000;.…”
Section: Treatment Modalitiesmentioning
confidence: 99%
“…To the authors' knowledge, nine double-blind, placebo-controlled trials of single-dose secretin (Carey et al, 2002;Coniglio, Lewis, Lang, & Burns, 2001;Corbett, Khan, Czapansky-Beilman, & Brady, 2001;Dunn-Geier, Ho, Auersperg, & Coyle, 2000;Kern, Miller, Evans, & Trivedi, 2002;Malloy et al, 2002;Owley et al, 2001;Sandler et al, 1999;Unis et al, 2002), two double-blind, placebo-controlled studies with multiple secretin doses (Roberts, Weaver, Brian, & Bryson, 2001;Sponheim, Oftedal, & Helverschou, 2002), two open-label single-dose trials (Chez, Buchanan, & Bagan, 2000; and one study of the impact of secretin on sleep in autistic children have been completed (Honomichl, Goodlin-Jones, Burnham, Hansen, & Anders, 2002). The two open-label trials, combined, included 44 autistic children and 34 children with PDD not otherwise specified (Chez et al, 2000;.…”
Section: Treatment Modalitiesmentioning
confidence: 99%
“…However, defended their sample as representative of those reported in the literature with respect to varied drug regimens. Moreover, in other studies reviewed in this article that also reported on-going pharmacotherapy with their participants (Dunn-Geier et al, 2000;Owley et al, 1999Owley et al, , 2001Sandler et al, 1999), no evidence was found for the differential efficacy of secretin. Corbett et al (2001) also used a randomized, double-blind, placebo-controlled crossover design to examine the effects of porcine secretin in 12 children with autism.…”
Section: Research Comparing Synthetic Secretin To Placebomentioning
confidence: 65%
“…That these symptoms are pervasive, in contrast to the more limited impact of other physical or mental disabilities (Herbert et al, 2002), may only intensify parents' desperation to find relief. Dunn-Geier et al (2000) suggest that early positive reports of the benefits of secretin by a parent may have increased its initial attractiveness and perceived utility. Hope for the drug's efficacy may also have been high since it is a natural substance found in the human body and its adverse effects appear minimal; thus, it may be seen as relatively safe, and by extension, possibly helpful.…”
Section: Discussionmentioning
confidence: 99%
“…Following the publication of the results of Horvath et al's study, an explosion of interest in using secretin as a treatment found its way to the Internet. However, numerous scientific studies have found no significant benefit from the use of secretin as compared to the use of a placebo (Coniglio et al, 2001;Coplan et al, 2003;Dunn-Geier et al, 2000;Molloy et al, 2002;Sandler et al, 1999).…”
Section: Biomedical Approachesmentioning
confidence: 99%